The Alterations in and the Role of the Th17/Treg Balance in Metabolic Diseases - Zhang, Siwen; Gang, Xiaokun; Yang, Shuo; Cui, Mengzhao; Sun, Lin; Li, Zhuo; Wang, Guixia (Frontiers in Immunology, 2021)
Chronic inflammation plays an important role in the development of metabolic diseases. These include obesity, type 2 diabetes mellitus, and metabolic dysfunction-associated fatty liver disease. The proinflammatory environment maintained by the innate immunity, including macrophages and related cytokines, can be influenced by adaptive immunity. The function of T helper 17 (Th17) and regulatory T (Treg) cells in this process has attracted attention. The Th17/Treg balance is regulated by inflammatory cytokines and various metabolic factors, including those associated with cellular energy metabolism. The possible underlying mechanisms include metabolism-related signaling pathways and epigenetic regulation. Several studies conducted on human and animal models have shown marked differences in and the important roles of Th17/Treg in chronic inflammation associated with obesity and metabolic diseases. Moreover, Th17/Treg seems to be a bridge linking the gut microbiota to host metabolic disorders. In this review, we have provided an overview of the alterations in and the functions of the Th17/Treg balance in metabolic diseases and its role in regulating immune response-related glucose and lipid metabolism.